Effect of Risk Factors on LV Systolic Dysfunction After Acute ST Elevation Myocardial Infarction - Khalid, Muhammad Sarwar; Goher, Fouzia; Ali, Asif; Javaid, Aaqib; Sarwar, Zoobia (Biological and Clinical Sciences Research Journal, 2025)
Left ventricular (LV) systolic dysfunction is a common complication following acute ST-elevation myocardial infarction (STEMI), particularly anterior wall infarctions. Several modifiable and non-modifiable cardiovascular risk factors, including diabetes, hypertension, smoking, obesity, and family history, have been implicated in the development of post-infarction LV dysfunction. However, the independent predictive value of these risk factors remains unclear in specific populations such as those in Pakistan. Objective: To assess the effect of major cardiovascular risk factors on the development of LV systolic dysfunction in patients presenting with a first episode of anterior STEMI. Methods: This observational cross-sectional study was conducted at the Department of Cardiology, Pervaiz Elahi Institute of Cardiology, Bahawalpur, Pakistan, over six months (July 2023 to January 2024). A total of 114 patients aged 25–70 years with first anterior STEMI were enrolled. Clinical and demographic data were recorded, and LV function was evaluated via echocardiography within 72 hours of admission. LV systolic dysfunction was defined as an ejection fraction <40%. Statistical associations between risk factors and LVD were assessed using chi-square tests. Results: The mean age of the cohort was 42.62 ± 10.13 years; 59.6% were male. Common risk factors included smoking (40.4%), diabetes (29.8%), hypertension (50%), and obesity (40.4%), while 59.6% had a positive family history of ischemic heart disease. LV systolic dysfunction was present in 20.2% of patients. No statistically significant association was found between LVD and age, gender, smoking, diabetes, hypertension, obesity, or family history (p > 0.05 for all). Conclusion: Although traditional cardiovascular risk factors were prevalent in patients presenting with anterior STEMI, none demonstrated a statistically significant association with early LV systolic dysfunction in this cohort. These findings suggest that additional pathophysiological or genetic factors may contribute to post-infarction LV impairment, underscoring the need for broader risk assessment and longitudinal studies in South Asian populations.